Molecular probes for autofluorescence-free optical imaging - Jiang, Yuyan (2022)
Optical imaging is an indispensable tool in clinical diagnostics and fundamental biomedical research. Autofluorescence-free optical imaging, which eliminates real-time optical excitation to minimize background noise, enables clear visualization of biological architecture and physiopathological events deep within living subjects. Molecular probes especially developed for autofluorescence-free optical imaging have been proven to remarkably improve the imaging sensitivity, penetration depth, target specificity, and multiplexing capability. In this Review, we focus on the advancements of autofluorescence-free molecular probes through the lens of particular molecular or photophysical mechanisms that produce long-lasting luminescence after the cessation of light excitation. The versatile design strategies of these molecular probes are discussed along with a broad range of biological applications. Finally, challenges and perspectives are discussed to further advance the next-generation autofluorescence-free molecular probes for in vivo imaging and in vitro biosensors.